2021
DOI: 10.1111/jfpp.16216
|View full text |Cite
|
Sign up to set email alerts
|

The impact of raspberry and blueberry extract on the microbial and lipid oxidative stability of calcium and chicken protein fortified composite chocolate

Abstract: A study was carried out to improve the functional and nutritive value of a composite chocolate using plant and animal ingredients. The aim was to formulate a composite chocolate with a favorable nutritional profile, improved storage stability, and melting resistance and a reduced cariogenicity using chicken protein powder (CPP), plant extracts, animal fat, and calcium lactate, respectively. The products were analyzed for quality parameters on 0, 2, 4, and 6‐months of storage (4 ± 1°C). The addition of optimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…In addition, cocoa treatment has been found to significantly increase GSH levels in liver tissue and heart tissue of male Albino Wistar rats [ 55 ]. Furthermore, chocolate containing raspberry and blueberry extracts led to significantly decreased TBARS levels [ 56 ]. Moreover, our research group has reported that methanolic extracts of Rosa canina decreased ROS and increased GSH levels in human endothelial cells [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, cocoa treatment has been found to significantly increase GSH levels in liver tissue and heart tissue of male Albino Wistar rats [ 55 ]. Furthermore, chocolate containing raspberry and blueberry extracts led to significantly decreased TBARS levels [ 56 ]. Moreover, our research group has reported that methanolic extracts of Rosa canina decreased ROS and increased GSH levels in human endothelial cells [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…One viable strategy to prevent lipid oxidation and to extend the shelf-life of cocoa spreads is addition of polyphenol-rich plant extracts. Indeed, addition of up to 3% of raspberry and blueberry extract significantly increased antioxidant potential and lipid oxidative stability of chocolate [ 43 ] supporting viability of such strategy.…”
Section: Resultsmentioning
confidence: 99%
“…The addition of 3.0% raspberry and blueberry extract in chicken protein-fortified composite chocolate significantly increased antioxidant potential, reduced lipid oxidation, and improved microbial and sensory attributes Kaur et al (2022) Propolis, sage and lavender…”
Section: Raspberry and Blueberrymentioning
confidence: 99%